Sezary syndrome in a young retropositive male: A rare case report (Indian Journal of Case Reports, 2019)
Sezary syndrome, a rare disease, is the leukemic counterpart of mycosis fungoides accounting for less than 5% of cutaneous lymphomas. Very few case reports have been published of Sezary syndrome/mycosis fungoides presenting in young male and with coexisting HIV. We present a case of a 23-year-old retropositive male presenting with Sezary syndrome which is very rare. The present case highlights the fact that Sezary syndrome can rarely present in young and retropositive patients. It should be kept in differential diagnosis if a patient presents with erythroderma, generalized lymphadenopathy and characteristic peripheral smear findings. A multimodal approach involving flow cytometry, skin biopsy and fine needle aspiration cytology (FNAC) is required for arriving at a definite diagnosis.